Testis developmental related gene 1 regulates the chemosensitivity of seminoma TCam‐2 cells to cisplatin via autophagy. Issue 11 (9th September 2019) - Peng, Dongyi; Wei, Jingchao; Gan, Yu; Yang, Jianfu; Jiang, Xianzhen; Kitazawa, Riko; Xiang, Yali; Dai, Yingbo; Tang, Yuxin
Abstract: We previously identified testis developmental related gene 1 (TDRG1), a gene implicated in proliferation of TCam‐2 seminoma cells. Recent evidence has revealed that autophagy influences the chemosensitivity of cancer cells to chemotherapy. However, whether TDRG1 protein regulates autophagy in seminoma cells and influences their sensitivity to cis ‐dichlorodiammine platinum (CDDP) remains unknown. In this study, we used TCam‐2 cells and male athymic BALB/c nude mice with xenografts of TCam‐2 cells to investigate autophagy, cell viability, apoptosis and the p110β/Rab5/Vps34 (PI3‐kinase Class III) pathway under the conditions of TDRG1 overexpression or knockdown and with or without CDDP treatment. We found that TDRG1 upregulation promoted autophagy in both TCam‐2 cells and seminoma xenografts via p110β/Rab5/Vps34 activation. Inhibition of autophagy reduced cell viability and promoted apoptosis during CDDP treatment of TCam‐2 cells. Similarly, TDRG1 knockdown inhibited autophagy, reduced cell viability and promoted apoptosis during CDDP treatment of TCam‐2 cells. TDRG1 knockdown inhibited tumour growth and promoted apoptosis in TCam‐2 cell xenografts, whereas TDRG1 overexpression had the opposite effect. According to these results, we propose that high expression of TDRG1 promotes autophagy through the p110β/Rab5/Vps34 pathway in TCam‐2 cells. TDRG1 overexpression promotes autophagy and leads to CDDP resistance, whereas TDRG1 knockdown inhibits autophagy and promotes chemosensitivity to CDDP both in vivo and in vitro. This study has uncovered a novel role of TDRG1 in reducing chemoresistance during CDDP treatment and provides potential therapeutic strategies for the treatment of human seminoma.